BReastfeeding Attitude and Volume Optimization (BRAVO) trial: study protocol for a randomized controlled trial. Issue 1 (December 2016) - Savitri, Ary; Idris, Nikmah; Indawati, Wahyuni; Saldi, Siti; Amelia, Dwirani; Baharuddin, Mohammad; Sastroasmoro, Sudigdo; Grobbee, Diederick; Uiterwaal, Cuno
Abstract Background A growing body of evidence shows the short-term benefits of breastfeeding, which include protection against infections, allergies, and lung diseases. However, evidence on the long-term benefits of breastfeeding is scarce and often conflicting. The BReastfeeding Attitude and Volume Optimization (BRAVO) trial is designed to study the effect of breastfeeding on early signs of later chronic diseases, particularly cardiovascular, respiratory, and metabolic risks later in life. In addition, the effectiveness of breastfeeding empowerment in promoting breastfeeding will also be evaluated. Methods/design This study is an ongoing randomized trial in Jakarta, Indonesia, that began in July 2012. Pregnant women are being screened for their breastfeeding plan in the third trimester, and those with low intention to breastfeed are randomly allocated to either receiving an add-on breastfeeding-optimization program or usual care. Primary outcomes include breastfeeding rate, lung function, and blood pressure during the first year of life and vascular/cardiac characteristics, which will be measured at the age of 4 to 5 years. Child growth and infection/illness episodes are measured, whereas cognitive testing is planned for the children at 5 years of age. Discussion To date, 784 women (80 %) have been randomized of the 1, 000 planned, with satisfactory completeness of the 1-year follow up (90.1 %). Included mothers are of lower socioeconomic status and more often have blue-collar jobs, similar to what was observed in the pilot study. Trial registration ClinicalTrials.gov, NCT01566812 . Registered on 27 March 2012.